Upaya Peningkatan Kemampuan Mengenal Huruf Abjad Menggunakan Media Stik Huruf Di RA Qurrota’ayun Desa Rancabungur - Pajririyah, Fadillah; Nisa, Syifa Zakiyatun; Karimah, Syahadah Albaqiyatul (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
This community service aims to improve the ability to recognize letters of the alphabet using letter stick media at RA Qurrata'ayun. The research methods used are demonstration and training methods which make the atmosphere of the learning process more fun, interesting and efficient. The results of this community service show that there is an increase in the ability to recognize alphabet letters in RA Qurrata'ayun students after learning to know letters using alphabet sticks. Therefore, alphabet stick media can be used as an alternative to improve the ability to understand letters in early childhood.